Fatores associados à incidência de sintomas depressivos em idosos em situação de vulnerabilidade social - Didoné, Letícia Souza (Universidade Federal de São Carlos, 2020)
Depression is a prevalent disease in the elderly and may present, as a risk factor for the development of frailty, a syndrome associated with comorbidity, disability, low perception of quality of life, social support and previous life habits. The objective of this study was to verify factors associated with depressive symptoms in elderly people living in neighborhoods of high social vulnerability in the city of São Carlos. It was a longitudinal, descriptive and exploratory study using the quantitative method. A sample was made up of 346 elderly people, collected from 2013 to 2015 and 2016 to 2018. The following instruments were used for data collection: sociodemographic characterization, Geriatric Depression Scale, Fried Phenotype, Medical Outcames Study - Suport Social Scale, Mini Mental State Examination, Katz and Lawton Index, International Physical Activity Questionnaire, Mini Nutritional Assessment and Automatic List of Smoking and Alcohol Consumption were applied. Of the interviewees, 110 elderly people indicated some level of depressive symptoms, most of whom were women (67.3%), with a mean age of 68.0 years. There were most participants with depressive symptoms who were smokers (58.4%), did not consume alcohol (86.7%), had nutritional risk (47.4%) and were sufficiently active (71.7%). The participants' cognition was altered for both groups without (61%) and with depressive symptoms (43%) and the perception of quality of life was satisfactory for both. In terms of functionality, most participants were active for activities of daily living. For social support, participants who showed some depressive symptom showed less in all evaluated supports. As for frailty, those who had a pre-frailty level, for the most part, did not indicate any depressive symptoms (62.2%). The prevalence of the analyzed variables was only significant in those evaluated from 2015 to 2018 for frailty (p-value: 0.00974). It was pointed out that being independent for functionality (OR: 0.93) and receiving informational support (OR: 0.96) are protective factors against depression. Belonging to the female gender (OR: 3.43) and consuming one or more cigarettes per day (OR: 2.47) indicated a predictive factor for depression. The impact of depression on the incidence of frailty was not statistically significant (RR: 1.46). It was concluded that depression was not associated with frailty. Being independent for functionality and receiving informational support in social support were protective factors against depression and belong to the female gender and cigarette consumption indicated predictive factors for depression.
Factores asociados a la incidencia de síntomas depresivos en personas mayores en situación de vulnerabilidad social.
Factors associated with the incidence of depressive symptoms in older people in a situation of social vulnerability
Keywords: Sintomas depressivos; Idosos; Fragilidade; Depressive symptoms; Older people; Frailty; CIENCIAS DA SAUDE::ENFERMAGEM